A direct fluorescent signal transducer embedded in a DNA aptamer paves the way for versatile metal-ion detection - Raducanu, Vlad-Stefan; Rashid, Fahad; Zaher, Manal S.; Li, Yanyan; Merzaban, Jasmeen S.; Hamdan, Samir M. (Sensors and actuators. B, Chemical, 2020)
•We developed a transducing technology that does not require any external reporter.•We designed a DNA-based aptamer that directly transduces potassium ions concentration to fluorescence change.•The aptamer binds potassium ions and undergoes conformational changes that can be sensed by the incorporated cyanine dye.•The sensor detects potassium in the low micro-molar range with high selectivity against a wide range of interfering ions. Using DNA aptamers as sensors for metal ions provide a variety of applications in biology and industry. Many of these sensors are based on guanine-rich DNA sequences that undergo conformational changes upon metal-ion binding. However, these sensors require an exogenous reporter that can recognize such DNA conformational changes and transduce the signal. Here, we bypass the exogenous reporter by embedding a signal transducer in the guanine-rich DNA aptamer that measures directly the DNA conformational changes upon metal-ion binding. Our signal transducer is an environmentally sensitive Cy3 fluorescent dye that is internally coupled to the DNA aptamer. We demonstrate the applicability of our embedded-signal transducer approach using a known potassium-responding aptamer. We next demonstrate the versatility of this approach by designing an aptamer sensor that can detect potassium ions in the low micro-molar range and with high selectivity against a wide range of ions including sodium. The aptamer accurately measured potassium ions concentration in a variety of aqueous and biological test samples. Our embedded-signal transducer approach will pave the way for the development of aptamer sensors for a variety of ligands.